Cardiovascular Disease Risk and Barriers to Physical Activity - Lisa Aditama; Dewi Rahmawati; Nani Parfati; Astrid Pratidina (The Indonesian Biomedical Journal, 2015)
BACKGROUND: The prevalence of obesity is increasing and tends to be higher in adult population groups who are also more educated and employed as a civil/military/police/oficers. This study aims to analyze cardiovascular disease (CVD) risk, perceptions about physical activity and barriers experienced to perform physical activity, also stage of change to physical activity.METHODS: The study design was an observational study, use qualitative methods with in-depth interviews and quantitative analysis CVD risk also stage of change to physical activity questionnaire.RESULTS: Framingham 10-years CVD risk of obese men in University of Surabaya was 11.97% (1.70 to 29.90) based on lipid profile and 13.90% (2.30 to 30.00) based on body mass index. Perception of obese men in University of Surabaya regarding physical activity had findings several barriers that can be grouped into time constraint, facility constraint, low motivation, and knowledge about physical activities.CONCLUSION: In this study we found that 10-years CVD risk of obese men in University of Surabaya can be categorized as medium risk. There are several barriers regarding life style modification for physical activity and exercise, whereas the subjects included in this study are quite ready to start the program, but improvement for the readiness before starting the program will still be needed.KEYWORDS: CVD risk, obese men, physical activity